Limitation of the Used Criteria for a Choice of Investment’s Variant in the Case of Small Hydropower Plants “Run-Of-The-River” - Kiranchev, Georgi (Research Papers, 2009)
The present study has for an object to analyze different possible criteria for a choice of an optimal variant of investment in small hydropower plants (SHPP) run-of-the-river and to give to potential investors a better idea to that should, and that should not pay attention, making his decisions.Colliding with the same problem - insufficient adequacy of the used methods and criteria of decision-making that often is an obstacle of decision-making, the author proposes his own vision to improvement of these methods and criteria. Interest to similar researches is due at least to the following reasons:During the last 15-16 years, the investments in SHPP in Bulgaria experiences a period of increasing interest. In the near future Bulgaria should reach 20 % of produced energy from renewable resources. Therefore, it is imperatively important, that it did not occur due to inefficient investment decisions. Complexity of a finding of optimal investment decisions occurs because of increase in decision variables. Whereas managing an already existing economic objects some part of these variables already have accepted his values and are already known, at a stage of finding of the investment decision it is necessary to find too the values of these variables.The mathematical instrument used allows the study to be useful to a broad audience of readers and does not demand a special mathematical knowledge.